ANALYSIS BETWEEN KNOWLEDGE AND ATTITUDES OF PARENTS REGARDING PROVIDING DOUBLE IMMUNIZATION AT THE MINASA UPA COMMUNITY HEALTH CENTER - Zabir, Nur Azizah; Jalaluddin, Syatirah; Rahim, Rosdianah; Iip Larasati; Fatmawati (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Immunization is the act of providing immunity against a disease by introducing specific substances into the body. The completeness of immunization can be influenced by several factors such as knowledge, attitudes, number of children, health worker attitudes, family support, distance from home, education, socio-cultural factors, and community trust. This study aims to determine the relationship between parental knowledge and attitudes toward administering double immunization in infants conducted at the Minasa Upa Community Health Center. The research method used was quantitative research with an observational analytic design with a cross-sectional approach and a non-probability sampling method with a purposive sampling technique, resulting in 85 samples. The study results found that most respondents had good levels of knowledge, with 46 respondents or 54.1%, and exhibited positive attitudes, with 43 respondents or 50.6%. The highest number of respondents who administered double immunization to infants were found to have good knowledge, accounting for 67.4%, with a P-value of 0.003. Meanwhile, the number of respondents who administered double immunization and had positive attitudes was 69.8%, with a P-value of 0.001. Based on this research, it can be concluded that there is a significant relationship between parental knowledge and attitudes towards the administration of double immunization in infants.